Platelet Mechanobiology Inspired Microdevices: From Hematological Function Tests to Disease and Drug Screening - Zhang, Yingqi; Jiang, Fengtao; Chen, Yunfeng; Ju, Lining Arnold (Frontiers in Pharmacology, 2022)
Platelet function tests are essential to profile platelet dysfunction and dysregulation in hemostasis and thrombosis. Clinically they provide critical guidance to the patient management and therapeutic evaluation. Recently, the biomechanical effects induced by hemodynamic and contractile forces on platelet functions become attract increasing attention. Unfortunately, the existing platelet function tests on the market do not sufficiently incorporate the topical platelet mechanobiology at play. Besides, they are often expensive and bulky systems with requirement of large sample volumes and long processing time. To this end, numerous novel microfluidic technologies emerge to mimic vascular anatomies, incorporate hemodynamic parameters and recapitulate platelet mechanobiology. These miniaturized and cost-efficient microfluidic devices shed light to high-throughput, rapid and scalable platelet function testing, hematological disorder profiling and antiplatelet drug screening. Moreover, the existing antiplatelet drugs often have suboptimal efficacy while incurring several adverse bleeding side effects on certain individuals. Encouraged by a few microfluidic systems that are successfully commercialized and applied to clinical practices, the microfluidics that incorporate platelet mechanobiology hold great potential as handy, efficient, and inexpensive point-of-care tools for patient monitoring and therapeutic evaluation. Hereby, we first summarize the conventional and commercially available platelet function tests. Then we highlight the recent advances of platelet mechanobiology inspired microfluidic technologies. Last but not least, we discuss their future potential of microfluidics as point-of-care tools for platelet function test and antiplatelet drug screening.